Rekontruksi Model Manajemen Rurukan dalam Upacara Adat - Suhaenah, Euis; Rochaeni, Ai Juju; Listiani, Wanda (PANGGUNG, 2016)
ABSTRACTÃÂ The research ÃÂ found the community ÃÂ management ÃÂ theory especiallyÃÂ  the rurukan ÃÂ manage- ment ÃÂ andÃÂ  the ÃÂ model of rurukan ÃÂ management ÃÂ in the ritual. Accredited Scientific ÃÂ journal or internationalÃÂ  ÃÂ reputation, ÃÂ memoir ÃÂ andÃÂ  the ÃÂ textbook for the cultural andÃÂ  art student ÃÂ are the output ÃÂ of this ÃÂ fundamental research.This ÃÂ research use the qualitative descriptive analysis, field observation ÃÂ is applied ÃÂ as theÃÂ  first ÃÂ step.The ÃÂ observation ÃÂ focusesÃÂ  on ÃÂ interview ÃÂ and ÃÂ event recording.The ÃÂ interview conducted with the performers, the prominent figures, ÃÂ and the artists that involved in the ritual.Depth ÃÂ interview ÃÂ technique through the main informan ÃÂ to get the validÃÂ  data for the solid result ÃÂ and comprehend description.The ÃÂ results ÃÂ of this research made reference to the Sundanese social-mindset in the manner ÃÂ of the Tritangtu concept in ritual tra- ditionÃÂ  through ÃÂ the three steps of the Rurukan ÃÂ discipline-management; ÃÂ Musyawarah ÃÂ (Confer- ence), ÃÂ Ngalaksanakeun ÃÂ (Implementation), ÃÂ and Wawarian ÃÂ (evaluation)also ÃÂ called MNW.ÃÂ Keywords: Community ÃÂ management, ÃÂ ritual tradition, ÃÂ rurukanÃÂ  ÃÂ management in SumedangÃÂ ÃÂ ABSTRAKÃÂ Penelitian ini menemukan teori manajemen komunitas khususnya manajemen rurukan dan model manajemen rurukan dalam upacara adat. Luaran penelitian Fundamental ini berupa jurnal ilmiah terakreditasi atau bereputasi internasional, laporan penelitian dan buku ajar bagi mahasiswa seni budaya. Penelitian ini menggunakan metode diskriptif analisis kualitatif, sebagai langkah awal pengumpulan data dilakukan dengan mengadakan observasi lapangan. Hal ini menitikberatkan pada pengamatan yang didukung dengan wawancara dan perekaman kejadian.Wawancara dilakukan dengan pelaku, tokoh yang terlibat langsung, dan tokoh seniman yang terlibat didalamnya.Teknik wawancara yang mendalam dengan cara memilih informan kunci guna mendapatkan validitas data yang menghasilkan deskripsi yang lebih utuh dan menyeluruh. Hasil penelitian merujuk pada pola pikir masyarakat Sunda dengan konsep Tritangtu. Dalam upacara adat ada 3 (tiga) tahapan dalam proses pengolaan manajemen rurukan; yakni musawarah, ngalaksana-keun, wawarian yang disebut MNW.ÃÂ Kata kunci: manajemen komunitas, upacara adat, manajemen rurukan, Sumedang